The case for internalising externalities in a sustainable rail asset base - Langdon, Mark; Gillott, Mark C.; Rodrigues, Lucélia Taranto; Parry, Tony (ICE Publishing, 2016)
Although the concept of sustainability and Sustainable development has tended to be mostly associated with the management of natural resources and the consequent environmental impact, the most accepted definition draws together its social, economic and environmental dimensions. The rail industry, as provider of a low carbon transport system, is well placed to have a significant role to play in promoting an environmental, economic and social balance that can be sustained and afforded for the foreseeable future.